2020
DOI: 10.1128/msystems.00502-20
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetic Factors Associated with Vaginal Microbiome Composition in Kenyan Women

Abstract: Bacterial vaginosis (BV) affects 20% of women worldwide and is associated with adverse reproductive health outcomes and increased risk for HIV. Typically, BV represents a shift in the vaginal microbiome from one that is dominated by Lactobacillus to one that is diverse. Persistent racial differences in BV and diverse vaginal microbiome composition overlap with racial disparities in risks for HIV and sexually transmitted infection, especially among women of African descent. Risk factors for BV and nonoptimal va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 64 publications
(69 reference statements)
2
12
0
Order By: Relevance
“…Our attempts to further understand the interaction between neutrophils and cervicovaginal microbiota revealed that genes associated with neutrophil activation, degranulation and responses were negatively correlated with G. vaginalis , positively correlated with L. iners, and were not associated with maternal age or BMI. This suggests that bacteria can modify the host response within the vaginal environment or vice versa, as supported by previous studies ( Beghini et al, 2013 ; Mehta et al, 2020 ; Florova et al, 2021 ). Metha et al reported the associations between vaginal species such as G. vaginalis and L. iners using GWAS, with pathways associated with innate immune responses and neutrophil degranulation.…”
Section: Discussionsupporting
confidence: 85%
“…Our attempts to further understand the interaction between neutrophils and cervicovaginal microbiota revealed that genes associated with neutrophil activation, degranulation and responses were negatively correlated with G. vaginalis , positively correlated with L. iners, and were not associated with maternal age or BMI. This suggests that bacteria can modify the host response within the vaginal environment or vice versa, as supported by previous studies ( Beghini et al, 2013 ; Mehta et al, 2020 ; Florova et al, 2021 ). Metha et al reported the associations between vaginal species such as G. vaginalis and L. iners using GWAS, with pathways associated with innate immune responses and neutrophil degranulation.…”
Section: Discussionsupporting
confidence: 85%
“…Microbial composition and dynamics can be influenced by a wide variety of factors including sexual and vaginal hygiene practices [7,33,34], hormonal and menstrual state (including effects of contraception) [20,35], pregnancy and childbirth [1,20], antibiotic exposure [36], smoking [37], genetics [37,38], and socioeconomic factors, the combined effects of which likely account for geographic and racial/ethnic differences between populations [11,12,[14][15][16]. Our study's strength relies on its analysis of an observational cohort of young women with few major exclusion criteria except HIV infection, major preexisting illness, or pregnancy [26,39].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, it is believed that the vaginal microbiome in black women does not play an important role in the pathogenesis of PTB, as it does in Caucasians and Asians ( Kindinger et al., 2017 ). Furthermore, the limited sample size, the time of sample collection, differences in the definition of PTB, ethnical and geographical variations, and differences in the methodology of strain identification, as well as complicated clinical conditions such as genetic abnormalities or a history of PTB, were confounding factors that impacted the results ( Ravel et al., 2011 ; Jespers et al., 2012 ; Mehta et al., 2020 ; Wells et al., 2020 ).…”
Section: Iners and Women Diseasesmentioning
confidence: 99%